2023
DOI: 10.1111/jgh.16449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age at diagnosis on long‐term prognosis in patients with intestinal Behçet's disease

Ji Young Chang,
Soo Jung Park,
Jae Jun Park
et al.

Abstract: Background and AimAlthough age at disease onset is considered to be a significant factor in the prognosis of Crohn's disease, little is known about its influence on the long‐term prognosis of those with intestinal Behçet's disease (BD). This study aimed to evaluate the long‐term clinical outcomes of patients with intestinal BD according to age of disease onset.MethodsPatients diagnosed with intestinal BD at < 18, 18–60, and > 60 years of age were classified into early‐onset, adult‐onset, and late‐onset g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Especially in younger patients, greater attention should be paid to disease progression, as multiple clinical evidences suggested that they often exhibit more severe clinical symptoms and poorer prognoses[ 74 - 76 ]. Patients with severe courses tend to be younger than those with mild courses[ 45 ], resulting in higher demand for outpatient, inpatient treatment, and intestinal surgery[ 75 ]. They are also more prone to postoperative recurrence[ 76 ].…”
Section: Prognosis Of Surgical Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in younger patients, greater attention should be paid to disease progression, as multiple clinical evidences suggested that they often exhibit more severe clinical symptoms and poorer prognoses[ 74 - 76 ]. Patients with severe courses tend to be younger than those with mild courses[ 45 ], resulting in higher demand for outpatient, inpatient treatment, and intestinal surgery[ 75 ]. They are also more prone to postoperative recurrence[ 76 ].…”
Section: Prognosis Of Surgical Interventionmentioning
confidence: 99%
“…They are also more prone to postoperative recurrence[ 76 ]. Therefore, it is essential to develop targeted treatment strategies for younger patients with intestinal BD, and to initiate immunosuppressant therapy early in the course of the disease[ 75 ].…”
Section: Prognosis Of Surgical Interventionmentioning
confidence: 99%